2020
DOI: 10.1002/jsfa.10769
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of non‐Saccharomyces species and aeration on sequential inoculation with Saccharomyces cerevisiae to produce lower alcohol Merlot wines from Washington state

Abstract: BACKGROUND Species of non‐Saccharomyces yeasts isolated from Washington vineyards were evaluated for their abilities to reduce alcohol contents of wines. As many of these yeasts benefit from some oxygen, the effect of limited aeration was also studied. RESULTS Although fermentations of a high sugar Merlot grape must (310 g L−1) did not reach dryness, inoculation of Metschnikowia chrysoperlae, Mt. pulcherrima, Meyerozyma guillermondii, Pichia kluyveri, or P. membranifaciens yielded in wines with lower amounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The lack of significant differences observed in the VA based on the utilization of NSY is in contrast with previously reported results. A previous study found that wines produced utilizing I. orientalis and P. kluyveri (same strains used in this work) contained higher concentrations of acetic acid compared to S. cerevisiae , regardless of aeration (Aplin & Edwards, 2020 ). Differences in results from the present to this previous study (Aplin & Edwards, 2020 ) could be attributed to altered fermentation conditions including lower cellar temperature (21°C) that favored NSY growth, and increased production of metabolites including acetic acid (Nevoigt & Stahl, 1997 ; Zott et al., 2008 ).…”
Section: Resultsmentioning
confidence: 74%
“…The lack of significant differences observed in the VA based on the utilization of NSY is in contrast with previously reported results. A previous study found that wines produced utilizing I. orientalis and P. kluyveri (same strains used in this work) contained higher concentrations of acetic acid compared to S. cerevisiae , regardless of aeration (Aplin & Edwards, 2020 ). Differences in results from the present to this previous study (Aplin & Edwards, 2020 ) could be attributed to altered fermentation conditions including lower cellar temperature (21°C) that favored NSY growth, and increased production of metabolites including acetic acid (Nevoigt & Stahl, 1997 ; Zott et al., 2008 ).…”
Section: Resultsmentioning
confidence: 74%
“…Nonetheless, recent studies have observed that low‐alcohol wines (9%–13% [v/v]) are more preferable to consumers due to increased public awareness of health and safety concerns concerning alcohol consumption (Bucher et al., 2018). Aplin and Edwards (2021) found that compared with the Merlot wine fermented using only S. cerevisiae , sequential inoculation with S. cerevisiae and P. kluyveri can reduce ethanol production by 0.4% (v/v). Rossouw and Bauer (2016) indicated that sequential inoculation with S. cerevisiae and H. uvarum can also reduce ethanol production by about 0.8% (v/v) in Pinotage wine.…”
Section: Resultsmentioning
confidence: 99%
“…Treatments H0S1, H0S2, and H0P0S2 had excessive accumulation of acetic acid (732-862 mg/L). Aplin and Edwards (2021) reported that H. uvarum produced high concentrations of acetic acid (1.39−1.80 g/L) in Merlot winemaking. In addition, it can be found that the increase in succinic acid content is related to inoculation of H. uvarum (Table 1).…”
Section: Effect Of Mixed Cultures In Organic Acids Content and Synthesismentioning
confidence: 99%
“…In particular, P. kluyveri is able to produce about 0.36 g of ethanol per g of sugar, with a yield that is about 22% lower than that of S. cerevisiae [ 79 ]. Wines with reduced ethanol concentrations without excessive acetic acid levels were produced by sequentially inoculating P. kluyveri with S. cerevisiae in high-sugar Merlot grape musts [ 123 ].…”
Section: Contribution Of Selected Yeasts To Emerging Winemaking Demandsmentioning
confidence: 99%